Mechanisms of action for the anti-obesogenic activities of phytochemicals - Bilal, Ahmad; Friar, Emily P.; Muhammad Sufyan, Vohra; Garrett, Michelle D.; Serpell, Christopher J.; Fong, Isabel Lim; Eng, Hwa Wong (Elsevier, 2020)
The prevalence of obesity is increasing rapidly globally and has recently reached pandemic proportions. It is a multifactorial disorder linked to a number of non-communicable diseases such as type-2 diabetes, cardiovascular disease, and cancer. Over-nutrition and a sedentary lifestyle are considered the most significant causes of obesity; a healthy lifestyle and behavioural interventions are the most powerful ways to achieve successful weight loss, but to maintain this in the long term can prove difficult for many individuals, without medical intervention. Various pharmacological anti-obesogenic drugs have been tested and marketed in the past and have been moderately successful in the management of obesity, but their adverse effects on human health often outweigh the benefits. Natural products from plants, either in the form of crude extracts or purified phytochemicals, have been shown to have anti-obesogenic properties and are generally considered as nontoxic and cost-effective compared to synthetic alternatives. These plant products combat obesity by targeting the various pathways and/or regulatory functions intricately linked to obesity. Their mechanisms of action include inhibition of pancreatic lipase activities, an increase in energy expenditure, appetite regulation, lipolytic effects, and inhibition of white adipose tissue development. In this review, we discuss the distinct anti-obesogenic properties of recently reported plant extracts and specific bioactive compounds, along with their molecular mechanisms of action. This review will provide a common platform for understanding the different causes of obesity and the possible approaches to using plant products in tackling this worldwide health issue.